Next Generation Sequencing and Animal Models Reveal SLC9A3R1 as a New Gene Involved in Human Age-Related Hearing Loss - Girotto, Giorgia; Morgan, Anna; Krishnamoorthy, Navaneethakrishnan; Cocca, Massimiliano; Brumat, Marco; Bassani, Sissy; La Bianca, Martina; Di Stazio, Mariateresa; Gasparini, Paolo (Frontiers in Genetics, 2019)
Age-related hearing loss (ARHL) is the most common sensory impairment in the elderly affecting millions of people worldwide. To shed light on the genetics of ARHL, a large cohort of 464 Italian patients has been deeply characterized at clinical and molecular level. In particular, 46 candidate genes, selected on the basis of genome-wide association studies (GWAS), animal models and literature updates, were analyzed by targeted re-sequencing. After filtering and prioritization steps, SLC9A3R1 has been identified as a strong candidate and then validated by “in vitro” and “in vivo” studies. Briefly, a rare (MAF: 2.886e-5) missense variant c.539G>A, p.(R180Q) was detected in two unrelated male patients affected by ARHL characterised by a severe to profound high-frequency hearing loss. The variant, predicted as damaging, was not present in healthy matched controls. Protein modelling confirmed the pathogenic effect of p.(R180Q) variant on protein’s structure leading to a change in the total number of hydrogen bonds. In situ hybridization showed slc9a3r1 expression in zebrafish inner ear. A zebrafish knock-in model, generated by CRISPR-Cas9 technology, revealed a reduced auditory response at all frequencies in slc9a3r1R180Q/R180Q mutants compared to slc9a3r1+/+ and slc9a3r1+/R180Q animals. Moreover, a significant reduction (5.8%) in the total volume of the saccular otolith (which is responsible for sound detection) was observed in slc9a3r1R180Q/R180Q compared to slc9a3r1+/+ (P=0.0014), while the utricular otolith, necessary for balance, was not affected in agreement with the human phenotype. Overall, these data strongly support the role of SLC9A3R1 gene in the pathogenesis of ARHL opening new perspectives in terms of diagnosis, prevention and treatment.